2009
DOI: 10.1021/jp907481q
|View full text |Cite
|
Sign up to set email alerts
|

Study on Initial Kinetics of CdSe Nanocrystals by a Combination of in Situ X-ray Absorption Fine Structure and Microfluidic Reactor

Abstract: The initial nucleation and growth processes of CdSe nanocrystals in a microfluidic reactor are studied by in situ extended X-ray absorption fine structure (EXAFS) in conjunction with UV−visible absorbance and photoluminescence spectra. On the basis of a surface reaction kinetics equation, the analytical expressions of the particle size and concentration are proposed. The surface reaction rate constant calibrated by UV−visible absorbance spectra at longer reaction time (>2.4 s) was used to estimate the particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…The formation of CdSe particles observed by EXAFS at 1.1 s (Sun et al, 2009) is confirmed by UV-vis absorption after 2.4 s (Fig. 5b).…”
Section: Formation Of Amorphous Nanoparticlessupporting
confidence: 58%
See 2 more Smart Citations
“…The formation of CdSe particles observed by EXAFS at 1.1 s (Sun et al, 2009) is confirmed by UV-vis absorption after 2.4 s (Fig. 5b).…”
Section: Formation Of Amorphous Nanoparticlessupporting
confidence: 58%
“…6b) clearly indicates good correlation of the two components, i.e. Se-Cd and Se-P pairs (Sun et al, 2009).…”
Section: Bond Formation Kineticsmentioning
confidence: 86%
See 1 more Smart Citation
“…There are two peaks at approximately 1.7Å and 2.3Å without a phase shift. Based on previous results [21,31,[39][40][41], the Cd-Se bond has a peak between 2.0 and 3.2Å in the Cd K-edge RSF function. In our results, there is a peak at approximately 2.3Å without a phase shift, which was confirmed to be from the Cd-Se bond.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 65%
“…Due to the advance in instrumentation and data analysis, in situ XAFS spectroscopy has been employed by several research groups to study the nucleation and growth of colloidal nanoparticles made of metals, semiconductors, and oxides . For example, Harada and co‐workers have extensively studied the synthesis of different metal nanoparticles through photoreduction of the corresponding metal precursors (e.g., H 2 PtCl 6 and K 2 PtCl 4 for Pt, RhCl 3 for Rh, PdCl 2 for Pd, AgClO 4 for Ag, HAuCl 4 for Au in an aqueous ethanol solution in the presence of poly( N ‐vinly‐2‐pyrrolidone) (PVP).…”
Section: In Situ X‐ray Absorption Fine Structure Spectroscopymentioning
confidence: 99%